Learning Theories According to Constructivism Theory - Nurhasnah, Nurhasnah; Sepriyanti, Nana; Kustati, Martin (Journal International Inspire Education Technology, 2024)
The education system carried out, especially in Indonesia, will often change according to the development and changes of the times, where all of that cannot be separated from the influence of technological developments and media that continue to reach developments every time, in learning to prepare for such things, a theory is needed, one of the theories that is also applied in the latest curriculum, namely the 2013 curriculum is the theory of constructivism. The purpose of this writing is to see how the theory of learning according to the theory of constructivism developed by Pieget and Vygotsky. The writing in this study uses the library method or Library Research. Where this paper finds the results that learning in constructivism theory, namely learning activities are active activities, where students build their own knowledge. Students seek their own meaning from what they learn, this is a process of adjusting new concepts and ideas to the existing framework in their minds. Piaget and Vygotsky cannot be separated from constructivism learning theory. However, there is a principle difference between Piaget's concept and Vygotsky's concept. If Piaget developed more schemata theory, Vygotsky developed more zone of development (ZD) theory and scaffolding.